Positive active material, positive pole piece, battery and electric device

By blending AxM11-a-bM2aM3bO2+c-dR1d with polyanionic compounds and controlling particle size distribution, the problem of difficult for the battery to take into account high energy density and good cycling performance is solved, and a longer service life and higher energy density are achieved.

CN119864384APending Publication Date: 2025-04-22CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311369049.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing batteries are difficult to take into account high energy density and good circulation performance, resulting in short service life.

Method used

A blended material of a first positive electrode active material including AxM11-a-bM2aM3bO2+c-dR1d and a second positive electrode active material of a polyanionic compound is adopted, and its particle size distribution is controlled to satisfy a specific volume-particle size ratio.

Benefits of technology

The gram capacity and compaction density of the positive electrode active material are improved, the energy density and cycling performance of the battery are improved, and the service life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864384A_ABST
    Figure CN119864384A_ABST
Patent Text Reader

Abstract

The invention discloses a positive active material, a positive pole piece, a battery and an electric device. The positive electrode active material comprises a first positive electrode active material and a second positive electrode active material, the first positive electrode active material comprises AxM11-a-bM2aM3bO2 + c-dR1d, 0.4 < = x < = 3, 0 < = a < = 0.9, 0 < = b < = 0.65,-0.25 < = c < = 0.25, 0 < = d < = 0.3, and A comprises an alkali metal element; m1, M2 and M3 respectively and independently comprise one or more elements in a group IIA, a group IIIA, a group IVA, a group VA, a group VIA, a group IVB, a group VB, a group VIB, a group VIIB, a group VIII, a group IB and a group IIB; r1 comprises one or more elements of F, S and P; a second positive electrode active material including a polyanionic compound; the volume particle sizes Dv10 (1) and Dv50 (1) of the first positive electrode active material and the volume particle sizes Dv10 (2) and Dv50 (2) of the second positive electrode active material meet the following conditions: Dv10 (1) / Dv10 (2) is greater than or equal to 3, Dv10 (1) / Dv50 (2) is greater than or equal to 2.5, and Dv50 (1) / Dv50 (2) is greater than or equal to 3. Therefore, the battery has relatively high energy density and relatively good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of batteries, and specifically, relates to positive electrode active materials, positive electrode sheets, batteries and electrical devices. Background Art

[0002] As an energy storage device, batteries are widely used in various fields. Take lithium-ion batteries as an example. They are green, environmentally friendly, high-energy, and low-carbon. They are not only used in energy storage power systems such as hydropower, thermal, wind, and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, and ships, as well as military equipment and aerospace and other fields. With the development of the current society, people's requirements for batteries are getting higher and higher. Summary of the invention

[0003] In view of the technical problems existing in the background technology, the present application provides a positive electrode active material, aiming to enable the battery to have both higher energy density and better cycle performance.

[0004] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, which includes:

[0005] The first positive electrode active material comprises: A x M1 1-a-b M2 a M3 b O 2+c-d R1 d , 0.4≤x≤3, 0≤a≤0.9, 0≤b≤0.65, -0.25≤c≤0.25, 0≤d≤0.3, A includes alkali metal elements; M1, M2, and M3 independently include one or more elements of Group IIA, Group IIIA, Group IVA, Group VA, Group VIA, Group IVB, Group VB, Group VIB, Group VIIB, Group VIII, Group IB, and Group IIB; R1 includes one or more elements of F, S, and P;

[0006] The second positive electrode active material includes: a polyanionic compound;

[0007] The particle size volume Dv10 of the first positive electrode active material (1) 、Dv50 (1) and the volume particle size Dv10 of the second positive electrode active material (2) 、Dv50 (2) satisfy:

[0008] Dv10 (1) / Dv10 (2) ≥3, Dv10 (1) / Dv50 (2) ≥2.5, Dv50 (1) / Dv50(2) ≥3.

[0009] The positive electrode active material of the present application has the following beneficial effects: Positive electrode active material A x M1 1-a-b M2 a M3 b O 2+c-d R1 d The polyanion-type positive electrode active material has high gram capacity and high compaction density, and has good cycle performance. Mixing the two and controlling the particle size distribution of the two to meet the given range requirements is beneficial to maintaining A x M1 1-a-b M2 a M3 b O 2+c-d R1 d The lattice stability during the charge and discharge cycle improves the cycle performance of the positive electrode active material and enhances the contribution of the first positive electrode active material to the compaction density of the positive electrode active material layer. On the other hand, the second positive electrode active material particles can be used to fill the gaps between the first positive electrode active material particles to increase the actual stacking density of the positive electrode active material, which is beneficial to further improve the energy density of the positive electrode active material, thereby helping the battery to have both high energy density and good cycle performance, thereby extending the battery life.

[0010] In some embodiments of the present application, the polyanionic compound comprises: A y M4 z [(X p O m ) n ]R2 e , wherein 1≤y≤9, 1≤z≤5, 1≤p≤7, 3≤m≤8, 0≤n≤5, 0≤e≤3, n and e are not 0 at the same time; M4 includes one or more elements from IVB group, VB group, VIB group, VIIB group, VIII group, IB group, and IIB group; X includes one or more elements from IVA group, VA group, and VIA group; R2 includes C, O, F, PO 4 The polyanionic compound that meets the given range conditions is beneficial to improving the cycle stability and cycle life of the positive electrode active material.

[0011] In some embodiments of the present application, A y M4 z [(X p O m ) n ]R2 eSatisfies at least one of the following conditions: 1≤y≤7; 1≤z≤4; 2≤p≤7; 3≤m≤7; 0≤n≤4; 1≤e≤2; M4 includes one or more elements of iron, vanadium, titanium, chromium, manganese, iron, molybdenum, cobalt, nickel, palladium, copper, and zinc, and may optionally include one or more elements of iron, vanadium, and manganese; X includes one or more elements of phosphorus, sulfur, and silicon. A y M4 z [(X p O m ) n ]R2 e Meeting the given conditions is conducive to further improving the cycle stability and cycle life of the positive electrode active material.

[0012] In some embodiments of the present application, the A y M4 z [(X p O m ) n ]R2 e Including A y Fe z (SO 4 ) n , A y Fe z (PO 4 ) n , A y V z (P 2 O 7 ) n , A y Fe z (PO 4 ) n F e One or more of. y M4 z [(X p O m ) n ]R2 e The composition satisfying the given range is beneficial to further improving the cycle stability and cycle life of the positive electrode active material.

[0013] In some embodiments of the present application, A x M1 1-a-b M2 a M3 b O 2+c-d R1 dSatisfy at least one of the following conditions: 0.02≤a≤0.9; 0.03≤b≤0.6, optionally, 0.03≤b≤0.4; -0.05≤c≤0.25, optionally, -0.05≤c≤0.15; 0.1≤d≤0.3; 1.8≤2+cd≤2; A includes sodium; M1, M2, M3 independently include one or more elements of lithium, titanium, vanadium, chromium, manganese, iron, molybdenum, cobalt, nickel, palladium, copper, zinc, tin, silicon, aluminum, selenium, optionally, M1 includes one or more elements of lithium, iron, manganese, nickel, cobalt, optionally, M2 includes one or more elements of manganese, iron, titanium, cobalt, and optionally, M3 includes one or more elements of manganese, nickel, zinc, titanium. Satisfying the given conditions is conducive to further improving the energy density of the positive active material.

[0014] In some embodiments of the present application, the A x M1 1-a-b M2 a M3 b O 2+c-d R1 d Including A x M1 1-a-b M2 a M3 b O 2 , A x FeO 2 , A x MnO 2 , A x Mn a Fe b O 2 , A x Ni 1-a-b Fe a Mn b O 2 , A x Ni a Ti b O 2 , A x Ni 1-a-b Mg a Mn b O 2 , A x Al 1-a-b Ni a Mn b O 2 , A x Li x′ Fe 1-a Mn a O 2 One or more of, wherein 0≤x′≤0.17. Meeting the given conditions is conducive to achieving a high pole piece compaction level and battery cell energy density.

[0015] In some embodiments of the present application, at least one of the following conditions is met: 3≤Dv10 (1) / Dv10 (2) ≤10, 2.5≤Dv10 (1) / Dv50 (2) ≤11.35、3.0≤Dv50 (1) / Dv50 (2) ≤24. Meeting the given conditions is conducive to further improving the cycle performance and energy density of the battery.

[0016] In some embodiments of the present application, at least one of the following conditions is met: Dv10 (1) 3μm~8μm, optional 3.6μm~7.6μm; Dv10 (2) 0.5μm~5μm, optional 0.95μm~3μm; Dv50 (1) 7μm~15μm, optional 7.2μm~12μm; Dv50 (2) The positive electrode active material meets the given conditions, which is conducive to taking into account the energy density and electrochemical performance of the positive electrode sheet and the battery at the same time.

[0017] In some embodiments of the present application, based on the total mass of the positive electrode active material, the mass percentage of the first positive electrode active material is W 1 The mass percentage of the second positive electrode active material is W 2 , W 1 and W 2 Satisfies: 2.25≤(ρ 1 ×W 1 ) / (ρ 2 ×W 2 )≤13.5, where ρ 1 is the true density of the first positive electrode active material, in g / cm 3 ρ 2 is the true density of the second positive electrode active material, in g / cm 3 Meeting the given conditions is conducive to further improving the cycle performance and gram capacity of the positive electrode active material, so that the battery has both high energy density and long service life.

[0018] In some embodiments of the present application, W 1 The range is 20% to 98%, and can be 75% to 90%. Meeting the given conditions is conducive to obtaining a higher voltage platform and gram capacity.

[0019] In some embodiments of the present application, W 2The content of the second positive electrode active material is 2% to 75%, and can be 10% to 70%. Meeting the given range is beneficial to inhibiting the phase transformation of the first positive electrode active material and reducing the adverse effect of excessive content of the second positive electrode active material on the gram capacity of the positive electrode active material.

[0020] In some embodiments of the present application, 1 4.40g / cm 3 ~5.25g / cm 3 , optional 4.60g / cm 3 ~5.05g / cm 3 ; and / or, 2 3.18g / cm 3 ~3.65g / cm 3 , optional 3.26g / cm 3 ~3.60g / cm 3 Meeting the given conditions is conducive to further improving the gram capacity of the positive electrode active material and increasing the energy density of the battery.

[0021] In some embodiments of the present application, W 2 =ρ 2 / (ρ 1 +ρ 2 ). Meeting the given conditions is conducive to further taking into account the cycle performance and gram capacity of the positive electrode active material.

[0022] In some embodiments of the present application, W 2 The content of the positive electrode active material is 10% to 40%, and can be 15.6% to 37%. Meeting the given conditions is conducive to further taking into account the cycle performance and gram capacity of the positive electrode active material.

[0023] In some embodiments of the present application, the volume particle size distribution curve of the positive electrode active material includes at least two peaks, the peak with the smallest particle size is recorded as peak I, and the remaining peaks are recorded as peak II, the particle size corresponding to the maximum peak intensity of peak I is 0.5μm to 5μm; and / or, the particle size corresponding to the maximum peak intensity of peak II is 3μm to 15μm. Meeting the given conditions is conducive to further improving the cycle performance of the positive electrode active material.

[0024] In some embodiments of the present application, the ratio of the integrated area of ​​the peak I to the total integrated area of ​​the peak II is (0.010-2.5): 1, and can be optionally (0.011-1.3): 1. Meeting the given conditions is conducive to taking into account both the compaction density and the cycle performance of the positive electrode active material, so that the battery has both high energy density and long service life.

[0025] The second aspect of the present application provides a positive electrode plate, which includes: the positive electrode active material of the first aspect of the present application.

[0026] In some embodiments of the present application, the positive electrode plate includes: a positive electrode current collector and a positive electrode active material layer provided on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material of the first aspect of the present application.

[0027] In some embodiments of the present application, 1540.25 mm 2 The weight of the positive electrode active material layer located on one side of the current collector is 200 mg to 400 mg. Meeting the given conditions is conducive to obtaining a higher energy density and reducing the risk of the pole piece being easily broken and the battery cell failing.

[0028] In some embodiments of the present application, the compaction density of the positive electrode active material layer is 1.6 g / cm 3 ~3.8g / cm 3 , optional 2.0g / cm 3 ~3.5g / cm 3 Meeting the given conditions is conducive to taking into account both the high energy density of the positive electrode and the operability of the preparation process.

[0029] In some embodiments of the present application, the porosity of the positive electrode active material layer is 20% to 50%, and can be 30% to 38%. Meeting the given conditions is beneficial to obtaining lower internal resistance of the electrode and better ion permeability, and is also beneficial to reducing the risk of accelerated self-discharge process.

[0030] In some embodiments of the present application, the shear force of the positive electrode sheet is 0.8 N / m to 1.2 N / m. Meeting the given conditions can make the electrode sheet have suitable brittleness, which is not only conducive to the winding of the positive electrode sheet, but also reduces the risk of demoulding and powder loss of the positive electrode active material layer, and can further reduce the risk of easy fracture due to excessive brittleness of the electrode sheet.

[0031] The third aspect of the present application provides a battery, which includes: the positive electrode plate of the second aspect of the present application; and / or, the positive electrode active material of the first aspect of the present application.

[0032] The fourth aspect of the present application provides an electrical device, which includes: the battery of the third aspect of the present application; and / or, the positive electrode plate of the second aspect of the present application; and / or, the positive electrode active material of the first aspect of the present application.

[0033] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0035] Figure 1 It is a schematic structural diagram of a battery according to one embodiment of the present application.

[0036] Figure 2 It is a schematic structural diagram of a battery module according to one embodiment of the present application.

[0037] Figure 3 It is a schematic diagram of the structure of a battery pack according to one embodiment of the present application.

[0038] Figure 4 is an exploded view of a battery pack according to one embodiment of the present application.

[0039] Figure 5 It is a schematic diagram of an embodiment of an electric device using a battery as a power source according to an embodiment of the present application.

[0040] Description of reference numerals:

[0041] 1: Battery; 2: Battery module; 3: Battery pack; 4: Upper case; 5: Lower case. DETAILED DESCRIPTION

[0042] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0043] Below, the embodiments of the positive electrode active material and its preparation method, positive electrode sheet, battery and electric device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0044] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit, and the selected lower limit and / or upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end value, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form an unambiguous range, and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, each individually disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0046] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0047] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S1 and S2, which means that the method may include steps S1 and S2 performed sequentially, or may include steps S2 and S1 performed sequentially. For example, the method may also include step S3, which means that step S3 may be added to the method in any order. For example, the method may include steps S1, S2 and S3, or may include steps S1, S3 and S2, or may include steps S3, S1 and S2, etc.

[0048] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0049] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0050] If there is no special explanation, in this application, the term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0051] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0052] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions. Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0053] With the continuous advancement of the green environmental protection theme, the application of batteries has penetrated into all aspects of life, including vehicles, electronic equipment, energy storage devices, etc. However, with the continuous promotion of battery applications, people's requirements for batteries are getting higher and higher, such as expecting batteries to have a long service life and high energy density. At present, there are many different improvement directions for improving the service life and energy density of batteries, such as extending the cycle life by improving the volume stability of the positive electrode and / or the negative electrode during the cycle; improving the energy density of the battery by changing the battery group margin, the compaction density of the active material layer, the type of active material, etc. How to make the battery have both high energy density and long cycle life is an important research direction at present.

[0054] In this application, by including A x M1 1-a-b M2 a M3 b O 2+c-d R1 d The first positive electrode active material and the second positive electrode active material including the polyanionic compound are mixed and the volume particle size distribution relationship of the two is controlled, which can combine the advantages of the two, and on the one hand, it is beneficial to maintain A x M1 1-a-b M2 a M3 b O 2+c-d R1 d The lattice stability during the charge and discharge cycle process improves the cycle performance of the positive electrode active material and enhances the contribution of the first positive electrode active material to the compaction density of the positive electrode active material layer. On the other hand, the first positive electrode active material and the second positive electrode active material can have a better particle size distribution, and the second positive electrode active material particles can be used to fill the gaps between the first positive electrode active material particles, so that the positive electrode active material has a higher actual stacking density, which is conducive to achieving a higher energy density, thereby helping the battery to have both a higher energy density and better cycle performance, thereby extending the battery life.

[0055] The positive electrode active material disclosed in the embodiment of the present application is suitable for secondary batteries, and the battery disclosed in the embodiment of the present application can be used in electrical equipment using the battery as a power source or various energy storage systems using the battery as an energy storage element. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.

[0056] The first aspect of the present application provides a positive electrode active material, which includes: a first positive electrode active material and a second positive electrode active material, wherein the first positive electrode active material includes: A x M1 1-a-b M2 a M3 b O 2+c-d R1 d, 0.4≤x≤3, 0≤a≤0.9, 0≤b≤0.65, -0.25≤c≤0.25, 0≤d≤0.3, A includes alkali metal elements; M1, M2, and M3 independently include one or more elements of Group IIA, Group IIIA, Group IVA, Group VA, Group VIA, Group IVB, Group VB, Group VIB, Group VIIB, Group VIII, Group IB, and Group IIB; R1 includes one or more elements of F, S, and P; the second positive electrode active material includes: a polyanionic compound; the volume particle size of the first positive electrode active material is Dv10 (1) 、Dv50 (1) and the volume particle size Dv10 of the second positive electrode active material (2) 、Dv50 (2) Meets: Dv10 (1) / Dv10 (2) ≥3, Dv10 (1) / Dv50 (2) ≥2.5, Dv50 (1) / Dv50 (2) ≥3.

[0057] For example, the value of x can be 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, etc., or can be a range consisting of any of the above values; the value of a can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.1, etc., or can be a range consisting of any of the above values; the value of b can be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0. 5, 0.55, 0.6, 0.65, etc., or any range thereof; c may be -0.25, -0.2, -0.15, -0.1, -0.05, 0, 0.05, 0.1, 0.15, 0.2, 0.25, etc., or any range thereof; d may be 0, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, etc., or any range thereof. Dv10 (1) / Dv10 (2) The value of can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 8, 9, 10, 11, 12, etc., which are greater than or equal to 3, or can be a range consisting of any of the above values; Dv10 (1) / Dv50 (2)The value of can be 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 8, 9, 10, 11, 12, 13, 15, etc., which is greater than or equal to 3, or can be a range consisting of any of the above values; Dv50 (1) / Dv50 (2) The value of can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, etc., which is greater than or equal to 3, or can be a range consisting of any of the above values. The first positive electrode active material that meets the above conditions is conducive to achieving a high pole sheet compaction density level and battery cell energy density.

[0058] Among them, Dv10 (1) Refers to the particle size corresponding to when the cumulative volume distribution percentage of the first positive electrode active material reaches 10%, that is, the volume content of particles of the first positive electrode active material less than or equal to this particle size accounts for 10% of the total particle volume; Dv50 (1) It refers to the particle size corresponding to the cumulative volume distribution percentage of the first positive electrode active material reaching 50% (i.e., the volume content of particles less than or equal to this particle size and the volume content of particles greater than or equal to the secondary particle size each account for 50% of the total particle volume). Accordingly, Dv10 (2) 、Dv50 (2) The particle sizes corresponding to the cumulative volume distribution percentage of the second positive electrode active material reaching 10% and the particle sizes corresponding to the cumulative volume distribution percentage of the second positive electrode active material reaching 50% are respectively Dv10 (1) 、Dv50 (1) 、Dv10 (2) 、Dv50 (2) The test can be carried out independently with reference to the standard GB / T 19077-2016 / ISO 13320:2009, using a laser particle size analyzer (Malvern Master Size 2000). The specific test process may include: taking an appropriate amount of the sample to be tested (the sample mass concentration is guaranteed to be 8% to 12% shading), adding deionized water, and ultrasonicating for 5 minutes (53kHz / 120W) to completely disperse the sample, and then measuring the sample according to the GB / T19077-2016 / ISO 13320:2009 standard.

[0059] Positive electrode active material A x M1 1-a-b M2 a M3 b O 2+c-d R1 dThe gram capacity is high, the compaction density is large, and it is easy to prepare, but there are many phase transitions during the charge and discharge process, and the structure is easily damaged when the alkali metal ions are deeply deintercalated; the polyanion type positive electrode active material has a good cycle life and the production cost is usually low, but its compaction density is small, and it is usually difficult to meet the needs of high energy density batteries. x M1 1-a-b M2 a M3 b O 2+c-d R1 d The first positive electrode active material and the second positive electrode active material including the polyanionic compound are mixed and used, which can not only combine the advantages of the two, but also help maintain the layered oxide A x M1 1-a-b M2 a M3 b O 2+c-d R1 d The lattice stability of the layered oxide is that when ions are deintercalated inside the layered oxide, they need activation energy to jump from the ground state site. The layered oxide lattice framework is prone to form areas where ions are difficult to diffuse, which increases the difficulty of ion transmission. After repeated cycles, the active material will also undergo phase changes and cause structural collapse. The polyanionic compound has a three-dimensional network structure that can quickly conduct ions. After mixing with the layered oxide, it can change the close-packed structure and lattice size of the lattice to a certain extent, reduce the barrier to ion diffusion, and maintain the lattice stability of the layered oxide. Further, the volume particle size Dv10 of the first positive electrode active material is made (1) 、Dv50 (1) and the volume particle size Dv10 of the second positive electrode active material (2) 、Dv50 (2) By satisfying the given range relationship, the second positive electrode active material particles can also be used to fill the gaps between the first positive electrode active material particles, thereby increasing the actual stacking density of the positive electrode active material, which is beneficial to further improve the energy density of the positive electrode active material, thereby helping the battery to have both higher energy density and better cycle performance, thereby extending the battery life.

[0060] In actual operation, the crystal structure of the positive electrode active material can be tested by XRD (for example, a Bruker AXS X-ray diffractometer can be used for testing, and the crystal structure analysis can be performed with reference to the standard PDF spectrum), and the element type and content of the positive electrode active material can be analyzed by energy dispersive spectrometer (EDS) and / or ICP element analysis to determine the positive electrode active material A. x M1 1-a-b M2 a M3 b O 2+c-d R1 dand the specific type of polyanionic compound; the volume particle size of the positive electrode active material can be tested to obtain a particle size distribution curve, based on the characteristics of the particle size distribution curve, such as the distribution position of the peak and the particle size corresponding to the maximum peak intensity, the particle size distribution is tested separately after sieving through a molecular sieve, and the crystal structure and microscopic morphology of the positive electrode active material are observed in combination with XRD testing, transmission electron microscopy and / or scanning electron microscopy (for example, transmission electron microscopy can be used to observe A x M1 1-a-b M2 a M3 b O 2+c-d R1 d The volume particle size Dv10 of the first positive electrode active material is determined by the interlayer spacing and other characteristics. (1) 、Dv50 (1) and the volume particle size Dv10 of the second positive electrode active material (2) 、Dv50 (2) The range and ratio relationship of the value of the real density can be analyzed in combination with the real density test. The real density refers to the mass of the unit "actual volume of solid matter (excluding open and closed pores and pores between particles)" in a dense state. The real volume can be obtained by testing first, and then the real density (g / cm2) can be obtained according to the real density = mass / real volume. 3 ), please refer to the national standard GB4472-84 for details.

[0061] The positive electrode active material of the present application has the following beneficial effects: on the one hand, it is conducive to maintaining A x M1 1-a- b M2 a M3 b O 2+c-d R1 d The lattice stability during the charge and discharge cycle process improves the cycle performance of the positive electrode active material and enhances the contribution of the first positive electrode active material to the compaction density of the positive electrode active material layer. On the other hand, the first positive electrode active material and the second positive electrode active material can have a better particle size distribution, and the second positive electrode active material particles can be used to fill the gaps between the first positive electrode active material particles, thereby increasing the actual stacking density of the positive electrode active material, which is beneficial to further improve the energy density of the positive electrode active material, thereby helping the battery to have both high energy density and good cycle performance, thereby extending the battery life.

[0062] It should be noted that A x M1 1-a-b M2 a M3 b O 2+c-d R1 dIn the formula, A, M1, M2, M3, and R1 may independently include one or more elements. Unless otherwise specified, when one or more of A, M1, M2, M3, and R1 include two or more elements, the numerical range of the corresponding stoichiometric number in the chemical formula is limited not only to the stoichiometric number of each element as the site, but also to the sum of the stoichiometric numbers of each element as the site. For example, taking M2 as an example, when M2 is two or more elements M2 1 、M2 2 ...M2 n When M2 1 、M2 2 ...M2 n The respective stoichiometric number a 1 、a 2 ……a n Each of them must fall within the numerical range of a specified in this application, and a 1 、a 2 ……a n Similarly, for the case where A, M1, M3, and R1 are two or more elements, the numerical range of the stoichiometric number of A, M1, M3, and R1 defined in this application also has the above meaning.

[0063] Furthermore, the positive electrode active material of the first aspect of the present application can further control the type of polyanionic compound, the volume particle size distribution, content ratio, true density, etc. of the first positive electrode active material and the second positive electrode active material on the basis of satisfying the above conditions to further optimize the performance of the positive electrode active material. That is, on the basis of satisfying the above conditions, one or more of the following conditions can also be optionally satisfied.

[0064] In some embodiments of the present application, the polyanionic compound may include: A y M4 z [(X p O m ) n ]R2 e , wherein 1≤y≤9, 1≤z≤5, 1≤p≤7, 3≤m≤8, 0≤n≤5, 0≤e≤3, n and e are not 0 at the same time; M4 may include one or more elements of IVB group, VB group, VIB group, VIIB group, VIII group, IB group, and IIB group; X may include one or more elements of IVA group, VA group, and VIA group; R2 may include C, O, F, PO 4 One or more of .

[0065] For example, the value of y can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, etc., or can be a range consisting of any of the above values; the value of z can be 1, 1.25, 1.5, 1.75, 2, 2.25, 2.5, 2.75, 3, 3.25, 3.5, 3.75, 4, etc., or can be a range consisting of any of the above values; the value of p can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, etc., or can be a range consisting of any of the above values; m The value of can be 3, 3.25, 3.5, 3.75, 4, 4.25, 4.5, 4.75, 5, 5.25, 5.5, 5.75, 6, 6.5, 7, 7.5, 8, etc., or can be any range consisting of the above values; the value of n can be 0, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc., or can be any range consisting of the above values; the value of e can be 0, 0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, 2.5, 2.75, 3, etc., or can be any range consisting of the above values. Wherein, A y M4 z [(X p O m ) n ]R2 e The specific composition can be determined by combining XRD test, energy dispersive spectrometer (EDS) and / or ICP element analysis. The polyanionic compound that meets the above given conditions is conducive to improving the lattice stability of the first positive electrode active material and improving the cycle performance of the positive electrode active material.

[0066] It should be noted that A y M4 z [(X p O m ) n ]R2 e In the formula, M4, X, and R2 may independently include one or more elements. Unless otherwise specified, when one or more of M4, X, and R2 include two or more elements, the numerical range of the corresponding stoichiometric number in the chemical formula is limited not only to the stoichiometric number of each element as the site, but also to the sum of the stoichiometric numbers of each element as the site. For example, taking M4 as an example, when M4 is two or more elements M4 1 、M4 2 ...M4 n When M4 1 、M4 2 ...M4 n The respective stoichiometric number z1 、z 2 ……z n Each of them must fall within the numerical range of z specified in this application, and z 1 、z 2 ……z n The sum also needs to fall within the numerical range. Similarly, for the case where M4 and R2 are two or more elements, the numerical range of the stoichiometric coefficients of M4 and R2 defined in this application also has the above meaning. It is understood that the specific type of A can be selected according to the application scenario of the positive electrode active material. For example, when the positive electrode active material is used in a sodium battery, A can be the Na element.

[0067] The composition of the polyanionic compound meeting the given range is beneficial to further improve the cycle stability and cycle life of the positive electrode active material.

[0068] In some embodiments of the present application, A y M4 z [(X p O m ) n ]R2 e At least one of the following conditions may be satisfied: 1≤y≤7; 1≤z≤4; 2≤p≤7; 3≤m≤7; 0≤n≤4; 1≤e≤2; M4 may include one or more elements of iron, vanadium, titanium, chromium, manganese, iron, molybdenum, cobalt, nickel, palladium, copper, and zinc, and may optionally include one or more elements of iron, vanadium, and manganese; X may include one or more elements of phosphorus, sulfur, and silicon. For example, A y M4 z [(X p O m ) n ]R2 e It may include but is not limited to phosphate materials and / or pyrophosphate materials. y M4 z [(X p O m ) n ]R2 e Meeting the given conditions can achieve a better compounding and combination with the first positive electrode active material, which is not only beneficial to improving the compaction density, but also beneficial to further improving the cycle stability and cycle life of the positive electrode active material.

[0069] In some embodiments of the present application, A y M4 z [(X p O m ) n ]R2 e Can include A y Fe z (SO4 ) n , A y Fe z (PO 4 ) n , A y V z (P 2 O 7 ) n , A y Fe z (PO 4 ) n F e One or more of .

[0070] Optionally, A y M4 z [(X p O m ) n ]R2 e Can include A y Fe z (PO 4 ) n , A y V z (P 2 O 7 ) n , A y Fe z (PO 4 )F e Phosphate and / or pyrophosphate doping has little effect on the long-range ordered structure of the layered oxide, its octahedral coordination is well maintained and the O 2p orbital energy level is reduced, which is beneficial to reduce the lattice oxygen release of the first positive electrode active material and improve the structural stability.

[0071] The composition of the polyanionic compound meeting the given range is beneficial to further improve the cycle stability and cycle life of the positive electrode active material.

[0072] In some embodiments of the present application, A x M1 1-a-b M2 a M3 b O 2+c-d R1 d Can include A x M1 1-a-b M2 a M3 b O 2 , A x FeO 2 , A x MnO 2 , A x Mna Fe b O 2 , A x Ni 1-a-b Fe a Mn b O 2 , A x Ni a Ti b O 2 , A x Ni 1-a-b Mg a Mn b O 2 , A x Al 1-a-b Ni a Mn b O 2 , A x Li x′ Fe 1-a Mn a O 2 One or more of , wherein 0≤x′≤0.17.

[0073] Understandably, A x M1 1-a-b M2 a M3 b O 2+c-d R1 d It can be a single material or a mixture of multiple positive electrode active materials satisfying the general formula. For example, A x M1 1-a-b M2 a M3 b O 2+c-d R1 d Can include A x M1 1-a-b M2 a M3 b O 2 , A x FeO 2 , A x MnO 2 , A x Mn a Fe b O 2 , A x Ni 1-a-b Fe a Mn b O 2 , A x Ni a Ti b O 2 , Ax Ni 1-a-b Mg a Mn b O 2 , A x Al 1-a-b Ni a Mn b O 2 , A x Li x′ Fe 1-a Mn a O 2 As some specific examples, A x M1 1-a-b M2 a M3 b O 2+c-d R1 d Can be Na x M1 1-a-b M2 a M3 b O 2+c-d R1 d , Na x M1 1-a-b M2 a M3 b O 2+c-d R1 d Can include Na x M1 1-a-b M2 a M3 b O 2 、Na x FeO 2 、Na x MnO 2 、Na x Mn a Fe b O 2 、Na x Ni 1-a-b Fe a Mn b O 2 、Na x Ni a Ti b O 2 、Na x Ni 1-a-b Mg a Mn b O 2 、Na x Al 1-a-b Ni a Mn b O 2 、Nax Li x′ Fe 1-a Mn a O 2 One or more of, wherein the value of x' can be 0, 0.02, 0.05, 0.07, 0.1, 0.12, 0.15, 0.17, etc., or can be a range consisting of any of the above values. x M1 1-a-b M2 a M3 b O 2+c-d R1 d The composition that meets the given conditions is conducive to achieving a high electrode compression level and battery cell energy density.

[0074] In some embodiments of the present application, A x M1 1-a-b M2 a M3 b O 2+c-d R1 d At least one of the following conditions may be met: 0.02≤a≤0.9; 0.03≤b≤0.6, optionally, 0.03≤b≤0.4; 0.05≤c≤0.25, optionally, 0.1≤c≤0.15; 0.1≤d≤0.3; 1.8≤2+cd≤2; A may include sodium element; M1, M2, and M3 may independently include one or more elements of lithium, titanium, vanadium, chromium, manganese, iron, molybdenum, cobalt, nickel, palladium, copper, zinc, tin, silicon, aluminum, and selenium; optionally, M1 may include one or more elements of lithium, iron, manganese, nickel, and cobalt; and further optionally, M2 may include one or more elements of manganese, iron, titanium, and cobalt; and further optionally, M3 may include one or more elements of manganese, nickel, zinc, and titanium. For example, the value of b can be 0.03, 0.05, 0.08, 0.1, 0.2, 0.25, 0.3, 0.35, 0.4, etc.; the value of c can be -0.05, -0.02, 0, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, etc.; the value of d can be 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, etc.; the value of 2+cd can be 1.8, 1.82, 1.85, 1.88, 1.9, 1.92, 1.95, 1.98, 2, etc., or can be a range consisting of any of the above values. A x M1 1-a-b M2 a M3 b O 2+c-d R1 d Meeting the given conditions is conducive to further improving the energy density of the positive electrode active material.

[0075] It should be noted that in the positive electrode sheet, battery or electrical device, alkali metal ions will be consumed due to the battery formation and circulation process, so the positive electrode active material A x M1 1-a-b M2 a M3 b O 2+c-d R1 d The alkali metal content x is less than 1 and / or the positive electrode active material A y M4 z [(X p O m ) n ]R2 e In the case where y is less than 1; in addition, if the positive electrode and the negative electrode are supplemented with lithium, the positive electrode active material A will be measured after the battery undergoes formation and cycling. x M1 1-a- b M2 a M3 b O 2+c-d R1 d The alkali metal content x is greater than 3 and / or the positive electrode active material A y M4 z [(X p O m ) n ]R2 e The case where y is greater than 7. In addition, the battery will be accompanied by the deintercalation and consumption of alkali metals during the charge and discharge process, and the molar content of alkali metals is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, the molar content of alkali metals is the initial state of the material, that is, the state before feeding. The positive electrode active materials are used in the battery system, and the molar content of alkali metals will change after charge and discharge cycles. In addition, during the preparation process of the positive electrode active materials, due to different process controls such as oxygen content or factors such as lattice oxygen release, there will be differences in the oxygen content in the positive electrode active materials. In the enumeration of positive electrode active materials in this application, the molar content of oxygen is only a theoretical state value, and the actual molar content of oxygen will fluctuate.

[0076] In some embodiments of the present application, the positive electrode active material may satisfy at least one of the following conditions: 3≤Dv10 (1) / Dv10 (2) ≤10, 2.5≤Dv10 (1) / Dv50 (2) ≤11.35、3.0≤Dv50 (1) / Dv50 (2) ≤24.

[0077] For example, Dv10 (1) / Dv10(2) The value of can be 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 8, 9, 10, etc., or can be a range consisting of any of the above values; Dv10 (1) / Dv50 (2) The value of can be 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 8, 9, 10, 11.35, etc., or can be a range consisting of any of the above values; Dv50 (1) / Dv50 (2) The value of can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, etc., or can be a range consisting of any of the above values. Making the volume particle size distribution of the first positive electrode active material and the second positive electrode active material satisfy the given range relationship is not only conducive to further improving the filling effect of the second positive electrode active material particles on the stacking gaps of the first positive electrode active material particles, improving the compaction density of the positive electrode sheet, and increasing the energy density of the battery cell, but also conducive to improving the structural stability of the positive electrode active material and improving the cycle performance.

[0078] The volume particle size distribution of the positive electrode active material meeting the given conditions is beneficial to further improve the cycle performance and energy density of the battery.

[0079] The positive electrode active material meeting the given conditions is conducive to further improving the compaction density of the positive electrode sheet and increasing the energy density of the battery cell.

[0080] In some embodiments of the present application, the positive electrode active material may satisfy at least one of the following conditions: Dv10 (1) Can be 3μm~8μm, optional 3.6μm~7.6μm; Dv10 (2) Can be 0.5μm~5μm, optional 0.95μm~3μm; Dv50 (1) Can be 7μm~15μm, optional 7.2μm~12μm; Dv50 (2) It can be 2μm to 5μm, and can be optionally 2.4μm to 3.2μm.

[0081] For example, Dv10 (1) It can be 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, etc., or can be a range consisting of any of the above values; Dv10 (2) It can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc., or can be a range consisting of any of the above values; Dv50(1) It can be 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc., Dv50 (2) It can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc., or it can be a range composed of any of the above values. The volume particle size changes of the first positive electrode active material and the second positive electrode active material will affect the compaction density after the two are mixed, and then affect the energy density of the battery cell. The volume particle size distribution of the first positive electrode active material and the second positive electrode active material meets the given conditions. On the one hand, the particle size grading and the arrangement after mixing can be improved. After the two are mixed, the second positive electrode active material particles can be used to better fill the stacking gaps of the first positive electrode active material particles to obtain an improved compaction density of the positive electrode sheet and the energy density of the battery cell. On the other hand, it is also beneficial to improve the stability of the positive electrode active material, so that the positive electrode active material has the advantages of a small internal conduction distance and few surface side reactions, which is beneficial to further improve the electrochemical performance of the positive electrode active material.

[0082] The positive electrode active material meeting the given conditions is beneficial to taking into account the energy density and electrochemical performance of the positive electrode sheet and the battery at the same time.

[0083] In some embodiments of the present application, based on the total mass of the positive electrode active material, the mass percentage of the first positive electrode active material is W 1 The mass percentage of the second positive electrode active material is W 2 , W 1 and W 2 Can satisfy: 2.25≤(ρ 1 ×W 1 ) / (ρ 2 ×W 2 )≤13.5, where ρ 1 is the true density of the first positive electrode active material, in g / cm 3 ρ 2 is the true density of the second positive electrode active material, in g / cm 3 .

[0084] For example, (ρ 1 ×W 1 ) / (ρ 2 ×W 2) can be 2.25, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, etc., or can be a range consisting of any of the above values. Increasing W1 is conducive to making the positive electrode active material have a higher gram capacity, and increasing the true density of the first positive electrode active material and the second positive electrode active material is conducive to increasing the compaction density of the positive electrode active material, both of which are conducive to improving the energy density of the battery. By making the true density of the first positive electrode active material and the second positive electrode active material and the mass proportion in the positive electrode active material meet the given range relationship, it is not only conducive to further obtaining a higher energy density, but also conducive to optimizing the relative usage range of the two, taking into account the gram capacity and cycle performance of the positive electrode active material. Among them, the test method of true density is as described in the previous section, and can be specifically carried out with reference to the national standard GB4472-84. For example, the particle size distribution curve of the positive electrode active material can be obtained first, sieved through a molecular sieve, and then the particle size distribution can be tested separately. The first positive electrode active material and the second positive electrode active material can be determined by combining XRD testing, transmission and / or scanning electron microscopy and performing distribution testing.

[0085] Meeting the given conditions is conducive to further improving the cycle performance and gram capacity of the positive electrode active material, so that the battery has both high energy density and long service life.

[0086] In some embodiments of the present application, W 1 It can be 20% to 98%, and optionally 75% to 90%.

[0087] For example, based on the total mass of the positive electrode active material, the mass percentage W of the first positive electrode active material is 1 It can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 98%, etc., or can be a range consisting of any of the above values. Compared with the second positive electrode active material, the first positive electrode active material has a higher gram capacity and relatively good conductivity. Making the mass percentage of the first positive electrode active material meet the given conditions is conducive to obtaining a higher voltage platform and gram capacity, and improving the energy density and electrochemical performance of the battery.

[0088] In some embodiments of the present application, W 2 It can be 2% to 75%, and optionally 10% to 70%.

[0089] For example, based on the total mass of the positive electrode active material, the mass percentage W of the second positive electrode active material is 2It can be 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, etc., or can be a range composed of any of the above values. Making the mass percentage of the second positive electrode active material in the positive electrode active material meet the given range is not only conducive to further inhibiting the phase transformation of the first positive electrode active material, improving the structural stability of the positive electrode active material, and improving the cycle performance, but also conducive to avoiding the adverse effects of excessive content of the second positive electrode active material on the gram capacity, internal resistance, etc. of the positive electrode active material. Optionally, W 1 It can be 20% to 98%, and can be 75% to 90% optionally. 2 It can be 2% to 75%, and can be optionally 10% to 70%. Meeting the given conditions is also beneficial to further taking into account the high energy density and long service life of the battery.

[0090] Among them, the mass percentages of the first positive electrode active material and the second positive electrode active material in the positive electrode active material can be estimated in combination with XRD and ICP tests. For example, the crystal form of the first positive electrode active material and the second positive electrode active material can be determined based on the characteristic peaks of the XRD spectrum. Optionally, the microstructure and lattice spacing of the positive electrode active material can be distinguished in combination with TEM and SEM tests. Furthermore, the composition and content of the two active substances can be analyzed in combination with ICP test of the main element content.

[0091] In some embodiments of the present application, W 2 It can be 10% to 40%, and can be optionally 15.6% to 37%. The mass percentage of the second positive electrode active material in the positive electrode active material satisfies the given range, which is beneficial to improving the structural stability of the first positive electrode active material, and is also beneficial to further avoid the negative impact on the gram capacity of the positive electrode active material due to the excessively high mass percentage of the second positive electrode active material, thereby further balancing the high energy density and long service life of the battery.

[0092] In some embodiments of the present application, W 2 =ρ 2 / (ρ 1 +ρ 2 ). 1 , 2 and W 2 Meeting the given conditions is conducive to further taking into account the cycle performance and gram capacity of the positive electrode active material, so that the battery has both high energy density and long service life.

[0093] In some embodiments of the present application, 1 Can be 4.40g / cm 3 ~5.25g / cm 3, optional 4.60g / cm 3 ~5.05g / cm 3 ; and / or, 2 Can be 3.18g / cm 3 ~3.65g / cm 3 , optional 3.26g / cm 3 ~3.60g / cm 3 .

[0094] For example, the true density of the first positive electrode active material is 1 Can be 4.40g / cm 3 4.50g / cm 3 4.60g / cm 3 , 4.70g / cm 3 4.80g / cm 3 , 4.90g / cm 3 , 5.0g / cm 3 , 5.10g / cm 3 , 5.20g / cm 3 , 5.25g / cm 3 etc., or can be a range consisting of any of the above values; 4.60 g / cm 3 ~5.05g / cm 3 In addition, the true density of the second positive electrode active material is 2 Can be 3.18g / cm 3 、3.26g / cm 3 、3.30g / cm 3 、3.35g / cm 3 、3.40g / cm 3 、3.45g / cm 3 、3.50g / cm 3 、3.55g / cm 3 、3.60g / cm 3 、3.65g / cm 3 etc., or can be a range consisting of any of the above values, optionally 4.60 g / cm 3 ~5.05g / cm 3 Increasing the true density of the first positive electrode active material and the second positive electrode active material is conducive to obtaining a higher energy density. By making the true density of the first positive electrode active material and the second positive electrode active material meet the given range, it is conducive to further improving the gram capacity of the positive electrode active material and improving the energy density of the battery.

[0095] In some embodiments of the present application, the volume particle size distribution curve of the positive electrode active material may include at least two peaks, the peak with the smallest particle size is recorded as peak I, and the remaining peaks are recorded as peak II. The particle size corresponding to the maximum peak intensity of peak I can be 0.5μm~5μm; and / or, the particle size corresponding to the maximum peak intensity of peak II can be 3μm~15μm.

[0096] For example, the particle size corresponding to the maximum peak intensity of peak I can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, etc., or can be a range consisting of any of the above numerical values; and / or, the particle size corresponding to the maximum peak intensity of peak II can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc., or can be a range consisting of any of the above numerical values. Among them, in the positive electrode active material, the volume particle size Dv10(2) and Dv50(2) of the second positive electrode active material are smaller than the volume particle size Dv10(1) and Dv50(1) of the first positive electrode active material. Peak I reflects the volume particle size distribution of the second positive electrode active material to a certain extent, and peak II reflects the volume particle size distribution of the first positive electrode active material to a certain extent. The particle sizes corresponding to the maximum peak intensities of peaks I and II respectively meet the given ranges, which is not only beneficial to improving the structural stability of the first positive electrode active material and reducing its phase transition during the charge and discharge process, but also beneficial to reducing the negative impact that the second positive electrode active material may have on the long-range ordered structure of the first positive electrode active material. In actual operation, the battery can be disassembled to obtain the positive electrode sheet, the positive electrode sheet can be cleaned to remove the residual electrolyte on the surface, the positive electrode sheet can be fully soaked in N-methylpyrrolidone (NMP) to remove the influence of the binder, and the powder mixture of the conductive agent and the positive electrode active material particles can be obtained by drying. The powder mixture is sieved (the particle size of the positive electrode active material particles and the particle size of the conductive agent are usually significantly different, with different orders of magnitude) to remove the conductive agent to obtain the positive electrode active material particles, and the volume particle size of the positive electrode active material is tested with the help of a laser particle size analyzer and a volume particle size distribution curve is drawn.

[0097] The volume particle size distribution curve of the positive electrode active material meeting the given conditions is conducive to further improving the cycle performance of the positive electrode active material.

[0098] In some embodiments of the present application, the ratio of the integrated area of ​​peak I to the total integrated area of ​​peak II may be (0.010-2.5):1, or may be (0.011-1.3):1.

[0099] For example, the ratio of the integrated area of ​​peak I to the total integrated area of ​​peak II can be 0.01, 0.05, 0.1, 0.3, 0.5, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, etc., or can be a range consisting of any of the above values. Alternatively, the ratio of the integrated area of ​​peak I to the total integrated area of ​​peak II can be (0.011-1.3):1, and can be further selected as (0.03-0.35):1.

[0100] The integral area of ​​peak I reflects the content of the second positive electrode active material to a certain extent. Making the ratio of the integral area of ​​peak I to the total integral area of ​​peak II satisfy the given range is beneficial to further improve the filling effect of the second positive electrode active material on the stacking gaps of the first positive electrode active material, improve the structural stability of the first positive electrode active material, and also help to reduce the negative impact that the second positive electrode active material may have on the long-range ordered structure of the first positive electrode active material.

[0101] The ratio of the integrated area of ​​peak I to the total integrated area of ​​peak II satisfies the given range, which is beneficial to taking into account both the compaction density and cycle performance of the positive electrode active material, so that the battery has both high energy density and long service life.

[0102] The second aspect of the present application provides a positive electrode plate, which includes: the positive electrode active material of the first aspect of the present application. The use of the positive electrode active material of the first aspect of the present application is conducive to the positive electrode plate to obtain a higher compaction density and better cycle performance, thereby facilitating the battery to have both high energy density and long service life.

[0103] In some embodiments of the present application, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material of the first aspect of the present application. Among them, the positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh and carbon-coated aluminum foil, and may be aluminum foil.

[0104] In some embodiments of the present application, 1540.25 mm 2 Based on the area of ​​the collector, the weight of the positive electrode active material layer located on one side of the current collector can be 200 mg to 400 mg.

[0105] For example, the weight of the positive electrode active material layer on one side of the current collector can be 200 mg, 220 mg, 240 mg, 260 mg, 280 mg, 300 mg, 320 mg, 340 mg, 360 mg, 380 mg, 400 mg, etc., or can be a range of any of the above values. The positive electrode active material layer on one side of the positive electrode sheet can be peeled off and weighed (with an accuracy of 0.0001 g), and the weight per 1540.25 mm2 can be obtained by combining the size of the peeled sample. 2 The weight of the positive electrode active material layer located on one side of the current collector in the area. Increasing the surface density of the positive electrode sheet can increase the energy density of the positive electrode sheet, so that the weight of the positive electrode active material layer located on one side of the current collector meets the requirements of the given range. On the one hand, it is beneficial for the positive electrode sheet to obtain a higher energy density. On the other hand, it can also reduce the risk of excessive brittleness of the electrode sheet, which may be caused by the high surface density of the positive electrode sheet, and the risk of electrode sheet breakage and battery cell failure.

[0106] Controlling the weight of the positive electrode active material layer on one side of the current collector to meet the given conditions is beneficial for obtaining a higher energy density and reducing the risk of electrode breakage and cell failure.

[0107] In some embodiments of the present application, the compaction density of the positive electrode active material layer can be 1.6 g / cm 3 ~3.8g / cm 3 , optional 2.0g / cm 3 ~3.5g / cm 3 .

[0108] For example, the compaction density of the positive electrode active material layer can be 1.6 g / cm 3 , 1.8g / cm 3 , 2.0g / cm 3 , 2.2g / cm 3 , 2.4g / cm 3 , 2.6g / cm 3 , 2.8g / cm 3 、3.0g / cm 3 、3.2g / cm 3 、3.4g / cm 3 、3.6g / cm 3 、3.8g / cm 3Etc., or can be a range consisting of any of the above values. The compaction density of the positive electrode active material layer can be obtained by testing the thickness of the positive electrode active material layer, peeling and weighing the positive electrode active material layer, and converting it. In the actual preparation process, the positive electrode slurry can be coated on the positive electrode current collector and then compacted under a pressure of 3 tons to obtain a positive electrode active material layer whose compaction density meets the given range conditions. Increasing the compaction density of the positive electrode active material layer can increase the energy density of the positive electrode sheet, so that the compaction density of the positive electrode active material layer meets the given conditions. On the one hand, it is beneficial to ensure a high particle stacking degree without destroying the physical structure of the positive electrode sheet and improve the energy density. On the other hand, it can also reduce the risk of abnormal problems such as cold pressing and tape breakage and roller sticking due to excessive compaction density. Optionally, the compaction density of the positive electrode active material layer can be 2.0g / cm 3 ~3.5g / cm 3 .

[0109] The compaction density of the positive electrode active material layer meets the given conditions, which is conducive to taking into account both the high energy density of the positive electrode sheet and the operability of the preparation process.

[0110] In some embodiments of the present application, the porosity of the positive electrode active material layer may be 20% to 50%, and may be optionally 30% to 38%.

[0111] For example, the porosity of the positive electrode active material layer can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., or can be a range composed of any of the above values. Optionally, the porosity of the positive electrode active material layer can be 30% to 38%. The porosity of the positive electrode active material layer can be tested with reference to the national standard GB / T 21650.2-2008. Increasing the porosity of the positive electrode active material layer is conducive to reducing the internal resistance of the electrode sheet and improving the permeability of ions. Making the porosity of the positive electrode active material layer meet the given conditions is conducive to obtaining a lower internal resistance of the electrode sheet and better ion permeability on the one hand, and on the other hand, it is also conducive to reducing the risk of accelerating the self-discharge process and obtaining better electrochemical performance.

[0112] In some embodiments of the present application, the shear force of the positive electrode sheet may be 0.8 N / m to 1.2 N / m.

[0113] For example, the shear force of the positive electrode sheet can be 0.8N / m, 0.85N / m, 0.9N / m, 0.95N / m, 1N / m, 1.05N / m, 1.1N / m, 1.15N / m, 1.2N / m, etc., or can be a range composed of any of the above values. The shear force of the positive electrode sheet can be tested with reference to GBT40388 2021. For example, the prepared electrode sample can be clamped on the fixture of the shear tester, maintaining an appropriate clamping force, and gradually increasing the shear force by controlling the force application device on the tester until the sample is damaged or the required shear force is reached. During the test, the shear force size and displacement of the sample are recorded, and the shear force-displacement curve is drawn. The shear strength of the sample is calculated according to the slope. In actual operation, the processed positive electrode sheet or the positive electrode sheet obtained by disassembling the battery can be tested. By making the shear force of the positive electrode sheet meet the given range, the electrode sheet can have appropriate brittleness, which is beneficial to the winding of the positive electrode sheet, reduces the risk of demolding and powder loss of the positive electrode active material layer, and further reduces the risk of easy fracture due to excessive brittleness of the electrode sheet.

[0114] In some embodiments of the present application, the positive electrode active material layer may also optionally include at least one of a binder, a conductive agent and other optional additives. As an example, the conductive agent may include but is not limited to one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. As an example, the binder may include but is not limited to one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB). As an example, other optional additives may include but are not limited to dispersants and residual alkali removers, dispersants may include but are not limited to superconducting carbon black and / or carbon nanotubes, and residual alkali removers may include but are not limited to oxalic acid and / or fumaric acid. These materials can be obtained commercially.

[0115] The third aspect of the present application provides a battery, which comprises: the positive electrode sheet of the second aspect of the present application; and / or, the positive electrode active material of the first aspect of the present application. Thus, the battery can have a higher energy density and a longer service life.

[0116] A battery is a battery that can be used again by recharging the active materials after discharge.

[0117] It can be understood that the battery proposed in the present application can be optionally a sodium battery, such as a sodium ion battery.

[0118] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.

[0119] [Negative electrode]

[0120] In a battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material. The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.

[0121] In some embodiments of the present application, the battery of the third aspect of the present application may be a sodium ion battery. In this case, the specific type of the negative electrode active material is not limited. Active materials known in the art that can be used for the negative electrode of a sodium ion battery may be used, and those skilled in the art may choose according to actual needs. As an example, the negative electrode active material may include but is not limited to at least one of sodium metal, carbon material, alloy material, silicon-based material, phosphorus-based material, etc. Specifically, the carbon material may include but is not limited to at least one of hard carbon, soft carbon, amorphous carbon, and nanostructured carbon material; the alloy material may include but is not limited to alloy materials formed by at least one of Si, Ge, Sn, Pb, and Sb; the silicon-based material may include but is not limited to silicon-carbon material, silicon dioxide, etc. These materials can all be obtained through commercial channels.

[0122] The negative electrode active material layer generally further optionally includes a binder and a conductive agent, the conductive agent is used to improve the conductivity of the negative electrode active material layer, and the binder is used to firmly bond the negative electrode active material and the binder to the negative electrode current collector. The present application does not specifically limit the types of conductive agents and binders, and they can be selected according to actual needs. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. As an example, the binder may include at least one of styrene butadiene rubber (SBR), styrene-butadiene rubber (SBCs), water-based acrylic resin (water-based acrylic resin) and carboxymethyl cellulose (CMC).

[0123] The negative electrode active material layer may also optionally include a thickener, such as carboxymethyl cellulose (CMC). However, the present application is not limited thereto, and the present application may also use other materials that can be used as thickeners for negative electrode sheets of lithium-ion batteries.

[0124] In some embodiments of the present application, the battery of the third aspect of the present application may be a sodium metal battery, in which case its negative electrode active material may include but is not limited to metallic sodium alone. For example, the negative electrode active material may also be an alloy formed by metallic sodium and various other metals or non-metallic elements.

[0125] In some embodiments of the present application, the battery of the third aspect of the present application can also be a negative electrode-free sodium metal battery. In this case, the negative electrode is composed of only a metal foil current collector without sodium metal on its surface. During the cycle process, only the sodium in the positive electrode is used, which is precipitated and stripped off in the form of sodium metal on the negative electrode side.

[0126] [Electrolyte]

[0127] The electrolyte may include an electrolyte salt and a solvent.

[0128] As an example, the electrolyte sodium salt may include but is not limited to at least one of sodium hexafluorophosphate, sodium difluorooxalatoborate, sodium tetrafluoroborate, sodium bisoxalatoborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate and sodium bis(trifluoromethylsulfonyl)imide.

[0129] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0130] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0131] [Isolation film]

[0132] As the above-mentioned isolation membrane, the present application has no special restrictions and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can include a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.

[0133] The embodiment of the present application has no particular limitation on the shape of the battery, which can be cylindrical, square or any other shape. Figure 1 A square-structured battery 1 is shown as an example.

[0134] In some embodiments, the battery may include an outer packaging for packaging the positive electrode sheet, the negative electrode sheet, and the electrolyte.

[0135] In some embodiments, the outer package may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.

[0136] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly. The electrode assembly is encapsulated in the accommodating cavity. The number of electrode assemblies contained in the battery can include one or more, which can be adjusted according to demand.

[0137] In some embodiments, the outer packaging of the battery may include a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.

[0138] The outer packaging of the battery may also include a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0139] In some embodiments, the battery may be either a single battery cell or a battery module or battery pack assembled from battery cells. The battery module or battery pack may contain multiple batteries, and the specific number may be adjusted according to the application and capacity of the battery module.

[0140] Figure 2 2 is an example of a battery module 2. Figure 2 In the battery module 2, the multiple batteries 1 can be arranged in sequence along the length direction of the battery module 2. Of course, they can also be arranged in any other manner. Further, the multiple batteries 1 can be fixed by fasteners.

[0141] The battery module 2 may also include a housing having a storage space, in which a plurality of batteries 1 are stored. In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0142] Figure 3 and Figure 4 The battery pack 3 is used as an example. Figure 3 and Figure 4The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.

[0143] The fourth aspect of the present application provides an electrical device, which includes: the battery of the third aspect of the present application; and / or, the positive electrode plate of the second aspect of the present application; and / or, the positive electrode active material of the first aspect of the present application.

[0144] Specifically, the battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships, satellites, and energy storage systems.

[0145] Figure 5 As an example of an electric device, the electric device includes a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. As another example, the electric device may include a mobile phone, a tablet computer, and a laptop computer. The electric device is usually required to be thin and light, and a battery may be used as a power source.

[0146] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0147] Example 1

[0148] 1. Preparation of secondary batteries

[0149] ① Preparation of positive electrode sheet:

[0150] The positive electrode active material, polyvinylidene fluoride (PVDF), conductive carbon black, and oxalic acid were mixed in a ratio of 94.3:2.3:3:0.4 and added to N-methylpyrrolidone (NMP), stirred, and dispersed to prepare a positive electrode slurry with a viscosity of 8000mPa·s to 15000mPa·s. The single-sided coating weight of the slurry was controlled at 300mg / 1540.25cm by double-sided double-cavity coating equipment. 2 , double-sided coating on aluminum foil, after double-sided coating is completed, drying, cold pressing, slitting, and preparing positive electrode sheets. Among them, the composition of the positive electrode active material is the first positive electrode active material Na0.67 Mn 0.67 Ni 0.33 O 2 and the second positive electrode active material NaFePO 4 The first positive electrode active material is mixed at a mass ratio of 75:25. The volume particle size Dv10(1) of the first positive electrode active material is 8 μm, and the volume particle size Dv50 (1) is 15μm, true density ρ 1 4.8g / cm 3 ; Volume particle size Dv10 of the second positive electrode active material (2) 0.5μm, volume particle size Dv50 (2) is 0.6μm, true density ρ 2 3.45g / cm 3 .

[0151] ② Preparation of negative electrode sheet:

[0152] The Cu foil was coated with CNT (carbon nanotube) coating on both sides with equal thickness as the deposition current collector, and the single-side coating thickness was about 2 μm.

[0153] ③ Preparation of soft-pack laminated batteries:

[0154] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene (PE) porous polymer film) are made into corresponding battery cells according to a Z-shaped stacking structure, and the battery cells are vacuum dried at 90°C for 12 hours, and then the positive and negative electrode tabs are ultrasonically welded. The positive electrode uses an aluminum tab and the negative electrode uses a nickel tab. The positive and negative electrode tabs are located on the same side of the battery cell. The battery cell after the tab welding is loaded into an aluminum-plastic film of a suitable size for top-side packaging. The conventional packaging temperature is 145°C, and the electrolyte is injected (electrolyte preparation: ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) are mixed in equal volumes, and fluoroethylene carbonate (FEC) is added, and LiPF6 is dissolved in the above-mentioned organic solvent to prepare an electrolyte with a concentration of 1 mol / L, wherein the mass percentage of DMC in the electrolyte is 5wt%), standing, formation, aging, exhaust, secondary sealing, and capacity testing are performed to obtain the prepared soft-pack laminated battery.

[0155] 2. Secondary battery testing

[0156] (a) Volume average particle size test

[0157] Equipment model: Malvern 2000 (MasterSizer 2000) laser particle size analyzer, specific test process: take an appropriate amount of the sample to be tested (the sample mass concentration is guaranteed to be 8-12% shading), add 20ml of deionized water, and ultrasonicate for 5min (53KHz / 120W) to ensure that the sample is completely dispersed, and then measure the volume particle size of the first positive electrode active material sample and the second positive electrode active material sample according to the GB / T19077-2016 / ISO 13320:2009 standard distribution.

[0158] (b) Test of initial capacity, cycle capacity retention rate and energy density of secondary batteries:

[0159] At 25℃, stand for 30min, discharge at 0.33C to 1.5V; at 25℃, stand for 30min, charge at 0.33C constant current to 3.65V, charge at constant voltage, cut-off current 0.05C; at 25℃, stand for 30min, discharge at 0.33C to 1.5V, the discharge capacity at this time is recorded as the initial capacity D 0 After that, let it stand for 30 minutes at 25℃, charge it to 3.65V at 0.33C constant current, charge it at constant voltage with a cut-off current of 0.05C, let it stand for 30 minutes, discharge it to 1.5V at 0.33C, and record the capacity as D n (n=1, 2...), repeat the previous process to perform charge and discharge cycles, and take the discharge capacity of the 1500th cycle as D 1500 , 1500 cycles discharge capacity retention rate = D 1500 / D 0 ×100%.

[0160] According to the initial capacity D 0 and the mass energy density of the secondary battery.

[0161] (c) Secondary battery discharge rate test

[0162] The following operations were performed in sequence: stand at 25°C for 30 minutes, discharge at 0.33C constant current to 1.5V; stand at 25°C for 1 hour, charge at 0.33C constant current to 3.65V, charge at constant voltage, and the cut-off current was 0.05C; stand at 25°C for 30 minutes, discharge at 0.33C constant current to 1.5V; stand at 25°C for 1 hour, charge at 0.33C constant current to 3.65V, charge at constant voltage, and the cut-off current was 0.05C; stand at 25°C for 30 minutes, discharge at 1C to 1.5V; stand at 25°C for 1 hour, charge at 0.33C constant current to 3.65V, charge at constant voltage, and the cut-off current was 0.05C; stand at 25°C for 30 minutes, discharge at 2C to 1.5V; stand at 25°C for 30 minutes. After a complete charge and discharge cycle, the capacity retention rate was calculated based on the discharge capacity at different discharge rates.

[0163] (d) DC impedance test

[0164] The following operations were performed in sequence: the battery was left standing at 25°C for 30 minutes, charged at 0.33C constant current to 3.65V, and charged at constant voltage with a cut-off current of 0.05C; left standing at 25°C for 5 minutes, and discharged at 0.33C to 50% SOC; left standing at 25°C for 1 hour, and discharged at 4C for 30 seconds; left standing at 25°C for 40 seconds, and the DC resistance DCR was calculated according to the formula DCR = ΔU / I 1 , where ΔU is the voltage change within 30s of discharge, in V; I is the discharge current, in A. Next, let it stand for 1h at 25℃, charge at 0.33C constant current to 3.65V, charge at constant voltage, with a cut-off current of 0.05C; let it stand for 5min at 25℃, discharge at 0.33C to 90% SOC; let it stand for 1h at 25℃, discharge at 4C for 30s; let it stand for 40s at 25℃, and calculate the DC resistance DCR according to the formula DCR=ΔU / I 2 .

[0165] Examples 1 to 25 and Comparative Examples 1 to 6

[0166] The differences between Examples 1 to 25 and Comparative Examples 1 to 6 are shown in Table 1.

[0167] Relevant tests were carried out on Examples 1 to 25 and Comparative Examples 1 to 6, and the test results are shown in Tables 2 to 4.

[0168]

[0169]

[0170]

[0171]

[0172] in conclusion:

[0173] Based on the data of Examples 1 to 25, Comparative Examples 1 to 6 and Tables 1 to 4, it can be seen that the scheme of the above-mentioned embodiments of the present application can improve the energy density and cycle performance of the positive electrode active material, so that the battery has a higher energy density and better cycle performance. In addition, in combination with Examples 1 to 8 and Table 4, it can be seen that the peak I and the peak II in the particle size distribution curve of the positive electrode active material meet the given range relationship, which is conducive to further obtaining a higher energy density and better cycle performance; in addition, in combination with Examples 1 to 8 and Table 2, it can be seen that further regulating the volume particle size relationship between the first positive electrode active material and the second positive electrode active material within the given range is conducive to further obtaining a higher energy density and better cycle performance. Optionally, 3≤Dv10 (1) / Dv10 (2) ≤10, 2.5≤Dv10 (1) / Dv50 (2) ≤11.35、3.0≤Dv50 (1) / Dv50 (2) ≤24. Further, in combination with Table 3, it can be seen that under the same conditions, the relative amount and true density of the first positive electrode active material and the second positive electrode active material can be further adjusted to further obtain higher energy density, better cycle performance, and lower internal resistance. Optionally, W 1 It can be 75% to 90%; alternatively, 2.25≤(ρ 1 ×W 1 ) / (ρ 2 ×W 2 )≤13.5.

[0174] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A positive electrode active material, characterized in that: include: The first positive electrode active material comprises: A x M1 1-a-b M2 a M3 b O 2+c-d R1 d , 0.4≤x≤3, 0≤a≤0.9, 0≤b≤0.65, -0.25≤c≤0.25, 0≤d≤0.3, A includes alkali metal elements; M1, M2, and M3 independently include one or more elements of Group IIA, Group IIIA, Group IVA, Group VA, Group VIA, Group IVB, Group VB, Group VIB, Group VIIB, Group VIII, Group IB, and Group IIB; R1 includes one or more elements of F, S, and P; The second positive electrode active material includes: a polyanionic compound; The volume particle size Dv10 of the first positive electrode active material (1) 、Dv50 (1) and the volume particle size Dv10 of the second positive electrode active material (2) 、Dv50 (2) satisfy: Dv10 (1) / Dv10 (2) ≥3、Dv10 (1) / Dv50 (2) ≥2.5、Dv50 (1) / Dv50 (2) ≥3。 2. The positive electrode active material according to claim 1, characterized in that The polyanionic compound comprises: A y M4 z [(X p O m ) n ]R2 e , wherein 1≤y≤9, 1≤z≤5, 1≤p≤7, 3≤m≤8, 0≤n≤5, 0≤e≤3, n and e are not 0 at the same time; M4 includes one or more elements of Group IVB, Group VB, Group VIB, Group VIIB, Group VIII, Group IB, and Group IIB; X includes one or more elements of Group IVA, Group VA, and Group VIA; R2 includes one or more of C, O, F, and PO4.

3. The positive electrode active material according to claim 2, characterized in that At least one of the following conditions is met: 1≤y≤7; 1≤z≤4; 2≤p≤7; 3≤m≤7; 0≤n≤4; 1≤e≤2; M4 includes one or more elements of iron, vanadium, titanium, chromium, manganese, iron, molybdenum, cobalt, nickel, palladium, copper, and zinc, and may optionally include one or more elements of iron, vanadium, and manganese; X includes one or more elements of phosphorus, sulfur, and silicon.

4. The positive electrode active material according to claim 2 or 3, characterized in that The A y M4 z [(X p O m ) n ]R2 e Including A y Fe z (SO4) n , A y Fe z (PO4) n , A y V z (P2O7) n , A y Fe z (PO4) n F e One or more of .

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that At least one of the following conditions is met: 0.02≤a≤0.9; 0.03≤b≤0.6, optionally, 0.03≤b≤0.4; -0.05≤c≤0.25, optionally, -0.05≤c≤0.15; 0.1≤d≤0.3; 1.8≤2+cd≤2; A includes sodium; M1, M2, and M3 independently include one or more elements of lithium, titanium, vanadium, chromium, manganese, iron, molybdenum, cobalt, nickel, palladium, copper, zinc, tin, silicon, aluminum, and selenium. Optionally, M1 includes one or more elements of lithium, iron, manganese, nickel, and cobalt. Optionally, M2 includes one or more elements of manganese, iron, titanium, and cobalt. Optionally, M3 includes one or more elements of manganese, nickel, zinc, and titanium.

6. The positive electrode active material according to any one of claims 1 to 5, characterized in that The A x M1 1-a- b M2 a M3 b O 2+c-d R1 d Including A x M1 1-a-b M2 a M3 b O2, A x FeO2、A x MnO2、A x Mn a Fe b O2, A x Ni 1-a-b Fe a Mn b O2, A x Ni a Ti b O2, A x Ni 1-a-b Mg a Mn b O2, A x Al 1-a-b Ni a Mn b O2, A x Li x′ Fe 1-a Mn a One or more of O2, wherein 0≤x′≤0.

17.

7. The positive electrode active material according to any one of claims 1 to 6, characterized in that At least one of the following conditions is met: 3≤Dv10 (1) / Dv10 (2) ≤10、2.5≤Dv10 (1) / Dv50 (2) ≤11.35、3.0≤Dv50 (1) / Dv50 (2) ≤24。 8. The positive electrode active material according to any one of claims 1 to 7, characterized in that At least one of the following conditions is met: Dv10 (1) 3μm~8μm, optional 3.6μm~7.6μm; Dv10 (2) 0.5μm~5μm, optional 0.95μm~3μm; Dv50 (1) 7μm~15μm, optional 7.2μm~12μm; Dv50 (2) It is 2μm~5μm, and can be optionally 2.4μm~3.2μm.

9. The positive electrode active material according to any one of claims 1 to 8, characterized in that Based on the total mass of the positive electrode active material, the mass percentage of the first positive electrode active material is W1, and the mass percentage of the second positive electrode active material is W2; W1 and W2 satisfy at least one of the following conditions: 2.25≤(ρ1×W1) / (ρ2×W2)≤13.5, wherein ρ1 is the true density of the first positive electrode active material, in g / cm 3 ; ρ2 is the true density of the second positive electrode active material, in g / cm 3 ; W1 is 20% to 98%, and can be selected as 75% to 90%; W2 is 2% to 75%, and can be optionally 10% to 70%.

10. The positive electrode active material according to claim 9, characterized in that ρ1 is 4.40 g / cm 3 ~5.25g / cm 3 , optional 4.60g / cm 3 ~5.05g / cm 3 and / or, ρ2 is 3.18 g / cm 3 ~3.65g / cm 3 , optional 3.26g / cm 3 ~3.60g / cm 3 .

11. The positive electrode active material according to claim 9 or 10, characterized in that: W2=ρ2 / (ρ1+ρ2); and / or, W2 is 10% to 40%, and can be optionally 15.6% to 37%.

12. The positive electrode active material according to any one of claims 1 to 11, characterized in that The volume particle size distribution curve of the positive electrode active material includes at least two peaks, the peak with the smallest particle size is recorded as peak I, and the remaining peaks are recorded as peak II. The particle size corresponding to the maximum peak intensity of peak I is 0.5μm to 5μm; and / or the particle size corresponding to the maximum peak intensity of peak II is 3μm to 15μm.

13. The positive electrode active material according to claim 12, characterized in that: The ratio of the integrated area of ​​the peak I to the total integrated area of ​​the peak II is (0.010-2.5):1, and can be optionally (0.011-1.3):

1.

14. A positive electrode sheet, characterized in that: include: The positive electrode active material according to any one of claims 1 to 13.

15. The positive electrode sheet according to claim 14, characterized in that: include: A positive electrode current collector and a positive electrode active material layer provided on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 13, and the positive electrode sheet satisfies at least one of the following conditions: 1540.25mm 2 The weight of the positive electrode active material layer located on one side of the current collector is 200 mg to 400 mg based on the area of ​​the positive electrode active material layer. The compaction density of the positive electrode active material layer is 1.6 g / cm 3 ~3.8g / cm 3 , optional 2.0g / cm 3 ~3.5g / cm 3 ; The porosity of the positive electrode active material layer is 20% to 50%, and can be optionally 30% to 38%; The shear force of the positive electrode sheet is 0.8 N / m to 1.2 N / m.

16. A battery, characterized in that: include: The positive electrode sheet according to claim 14 or 15; and / or, the positive electrode active material according to any one of claims 1 to 13.

17. An electrical device, characterized in that: include: The battery according to claim 16; and / or, the positive electrode sheet according to claim 14 or 15; and / or, the positive electrode active material according to any one of claims 1 to 13.